CODE SWITCHING USED BY LECTURERS IN THE STUDY PROGRAM OF ENGLISH LITERATURE OF UNIVERSITAS BRAWIJAYA - HIKMAH, EVY FAJRIATUL (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: sociolinguistics, code switching, lecturerThis study is aimed to find out the code switching used by lecturers in the Study Program of English Literature of Universitas Brawijaya. There were three problems of the study namely: (1) what are the types of code switching used by lecturers; (2) what are the reasons of code switching used by lecturers; and (3) what are the students’  perspective toward the code switching used by lecturers.This study used qualitative approach since the data being analyzed were in the form of the lecturers’ utterances when explaining the lesson in the classrooms. In achieving the purposes of the study, the writer applied theories of types and reasons of code switching by Hoffmann (1991).The writer found four types of code switching used by the lecturers such as intra-sentential (78.1%), inter-sentential (16.7%), emblematic switching (4.4%), and establishing continuity with the previous speaker (0.7%). In addition, there were six reasons of code switching used by the lecturers found such as intention of clarifying the speech content for interlocutor (59.4%), talking about particular topic (23%), interjection (7.5%), being emphatic about something (4%), expressing group identity (3.3%), and repeating used for clarification (2.8%). The writer also found two reasons based on the results of interview. First, there are some terms which are easier to be explained in English. The second is to make the discussion in the classroom run smoothly. Moreover, the lecturers’ switching give positive effects. According to the students’ opinion, they can enhance their understanding of the material taught through the lecturers’ code switching.The researcher suggests the next researchers who want to conduct a study about code switching to use different theories and objects. The next researchers are also expected to investigate the code switching phenomenon by combining with other theories such as gender. Then, the writer suggests the lecturers to use code switching as a useful strategy in teaching since it gives positive effects to the students’ understanding.